Milk Fat Globules Hamper Adhesion of Enterohemorrhagic Escherichia coli to Enterocytes: In Vitro and in Vivo Evidence - Douëllou, Thomas; Galia, Wessam; Kerangart, Stéphane; Marchal, Thierry; Milhau, Nadège; Bastien, Renaud; Bouvier, Marion; Buff, Samuel; Montel, Marie-Christine; Sergentet-Thevenot, Delphine (Frontiers in Microbiology, 2018)
Enterohemorrhagic Escherichia coli (EHEC; E. coli) are food-borne agents associated with gastroenteritis, enterocolitis, bloody diarrhea and the hemolytic-uremic syndrome (HUS). Bovine milk glycans have been shown to contain oligosaccharides which are similar to host epithelial cell receptors and can therefore prevent bacterial adhesion. This study aimed to describe interactions between EHEC O157:H7 EDL933 and O26:H11 21765 and Milk Fat Globules (MFGs) in raw milk and raw milk cheese, and the impact of MFGs on EHEC strains adhesion to the intestinal tract in vitro and in vivo. Both EHEC serotypes clearly associated with native bovine MFGs and significantly limited their adhesion to a co-culture of intestinal cells. The presence of MFGs in raw milk cheese had two effects on the adhesion of both EHEC serotypes to the intestinal tracts of streptomycin-treated mice. First, it delayed and reduced EHEC excretion in mouse feces for both strains. Second, the prime implantation site for both EHEC strains was 6 cm more proximal in the intestinal tracts of mice fed with contaminated cheese containing less than 5% of fat than in those fed with contaminated cheese containing 40% of fat. Feeding mice with 40% fat cheese reduced the intestinal surface contaminated with EHEC and may therefore decrease severity of illness.